Shear response of circular-in-square CFDST members: Experimental investigation and finite element analysis. (March 2022) - Duan, Li-Xin; Wang, Wen-Da; Xian, Wei; Shi, Yan-Li
Abstract: This paper firstly presented an experimental work of circular-in-square concrete-filled double-skin steel tubular (CFDST) members under lateral shear load. Sixteen circular-in-square CFDST specimens and four concrete-filled steel tubular (CFST) specimens were fabricated and tested. Crucial design parameters considered in this test including shear-span ratio ( m  = 0.4, 0.6, 0.8 and 1.0) and hollow ratio ( χ  = 0.46, 0.59, 0.67 and 0.82) were studied and discussed. The load-displacement curve ( P-Δ ), shear strain-load curve ( γ-P ), and failure mode of the tests were analyzed in detail. The testing results show that as the shear-span ratio increases, the shear capacity drops significantly with the change of failure modes from brittle shear failure to ductile bending failure. The hollow ratio is of primary importance in the study of shear strength for CFDST specimens. When m is 0.4–0.8, specimens with a larger the hollow ratio experience a lower shear capacity, and however when m  = 1.0, specimens with larger the hollow ratio exhibit a higher shear capacity. Furthermore, using experimental work presented in this study as a basis for model verification, corresponding finite element model was developed to further explore the mechanical properties of CFDST specimens subjected to shear load via using software ABAQUS. Finally, the expression was proposed for predicting the shear capacity of circular-in-square CFDST specimens, in which both the shear-span ratio and hollow ratio were considered. It can be found that the predictions are very compatible to the testing results from this study. Highlights: Very limited studies on the shear response of CFDST members have been carried out. Experimentally and numerically investigated the shear response of CFDST members. The effects of hollow ratio and shear-span ratio are considered and discussed. The calculation method of shear capacity for the tested specimens is proposed.